Music Ecosystem in Chile from Democratic Neoliberalization to Social Outburst, the Covid-19 Pandemic and Recent Political Reforms (Revista Argentina de Musicología, 2022)
This article describes the main historical and recent trajectories of the music ecosystem in Chile. At first, it explores some brief reflections on music trends in Chile in recent decades. Subsequently, and based on a review of studies and statistical figures available at the national level, it analyzes the consequences that the Covid-19 pandemic —and also the social outburst of October 2019— has generated in the logics of production, circulation and reception of the local music. Finally, the article focuses on establishing analytical guidelines on the trends that the music industry in Chile —and also globally— has been experiencing during the pandemic and how these transformations could be glimpsed in the coming decades. The article concludes with a reflection on the constitutional and political process underway in Chile, and how the current constitutional discussion on cultural rights can contribute to thinking about the future condition of Chilean music.
Keywords: music ecosystem; social outburst; pandemic; new constitution; Chile